Research on Cooperative Innovation Network Structure and Evolution Characteristics of Electric Vehicle Industry - Wu, Liping; Xu, Man (Sustainability, 2022)
The electric vehicle industry involves various technological cooperative innovations, meaning that electric vehicle companies must not only cooperate and innovate with similar enterprises in the same industry, but also collaborate with enterprises across the industry and research institutions (RIs). This paper empirically analyzed the structure and evolution characteristics of cooperative innovation networks, based on the patent application data in the field of electric vehicles from 2006 to 2021. It was found that the firm–firm intra-industry and inter-industry cooperative innovation networks, and firm–RI cooperative innovation networks have the characteristics of phased evolution in structure, and the network structure in the evolution process has similarities and differences. Furthermore, during the industrial formation period, inter-industry cooperative innovation focuses on the cooperation between the midstream and downstream industries of the industrial chain; but in the industrial growth period, inter-industry cooperative innovation has been widely extended to multiple industries in the upper, middle and lower reaches of the industrial chain. While the scale of intra-industry and industry–research institution cooperative innovation continues to expand with the development of the industry, the collaboration is concentrated in the five industries in the middle and downstream of the industrial chain. The research conclusion can provide a reference for different cooperative innovation partners of electric vehicles and other emerging industries to formulate differentiated policies.